2013
DOI: 10.1080/19338244.2012.750586
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Hepatitis B Vaccination Among Health Care Workers in Western Greece

Abstract: Health care personnel are at high risk for hepatitis B virus (HBV) transmission. The aim of the present study was to investigate hepatitis B (HB) knowledge and vaccination acceptance among health care personnel in southwestern Greece, using the Hepatitis B Vaccine Knowledge and Acceptance Questionnaire. One hundred eighty-three employees participated (71 males). Occupation (p < .001), higher education (p < .001), and vaccination (p = .007) were significantly related to HB knowledge. The rate of HBV vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
5
14
1
1
Order By: Relevance
“…49e53 In line with the literature, this study found that physicians are less likely to complete the full vaccine schedule than nurses. 54,55 This may be due to indolence and/or negligence of medical personnel, 56 and to a lack of awareness of the biological risk linked to their occupational duties. It is therefore necessary to incorporate educative measures as an integral part of an effective vaccination programme in order to raise HCWs' awareness of the importance of vaccination and the risks associated with nonvaccination.…”
Section: Discussionmentioning
confidence: 99%
“…49e53 In line with the literature, this study found that physicians are less likely to complete the full vaccine schedule than nurses. 54,55 This may be due to indolence and/or negligence of medical personnel, 56 and to a lack of awareness of the biological risk linked to their occupational duties. It is therefore necessary to incorporate educative measures as an integral part of an effective vaccination programme in order to raise HCWs' awareness of the importance of vaccination and the risks associated with nonvaccination.…”
Section: Discussionmentioning
confidence: 99%
“…40 In this study, according with the findings of a review on vaccination in Italian healthcare workers in 2010 and other national and international studies, vaccination coverage for hepatitis B is acceptable but still sub-optimal and figures for other vaccinepreventable diseases are quite low. 7,[11][12][13][14][15][16][30][31][32][33][34][35][36][37][38]41 Vaccination coverage for seasonal influenza is far from the objective of 75% to be achieved by 2015 as in the EU Council recommendation of December 2009. 42 Protection against measles, mumps, rubella and varicella is totally inadequate to prevent disease transmission among susceptible HCWs and nosocomial oubreaks.…”
Section: Discussionmentioning
confidence: 99%
“…30 In Belgium, in 2004, 84.9% of HCWs eligible for HB immunization had received the vaccine; 31 in France, in 2011, of 505 HCWs working in tertiary-care hospitals, 56.5% had been vaccinated against hepatitis B; 32 in South-Western Greece HB vaccination coverage was 70.9% in 2013. 33 Coverage for the other recommended vaccines is often very low and inadequate to prevent hospital epidemics. 32,34 In France, a study conducted in 2011 showed vaccination coverage of 18.8% for measles and mumps, 22.2% for rubella, 1.9% for varicella and 35.7% for tetanus-diphtheria.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HCP who worked in obstetrics and gynaecology, paediatrics, and emergency departments, infectious disease division, and postpartum nursing care centres had first priority (Taiwan Centers for Disease Control, 2013). Most existing studies on HCP immunisations mainly focused on influenza and Hep B vaccines and reported that HCP exhibited different behavioural patterns towards different vaccine types (Adekanle, Ndububa, Olowookere, Ijarotimi, & Ijadunola, 2015;Chambers et al, 2015;Karaivazoglou et al, 2014). Relevance to clinical practice: It is suggested using health education courses and mass media broadcasts at the individual and societal levels to raise awareness regarding the benefits of vaccines and enhance nurse' confidence in vaccination programs.…”
Section: Backg Rou N Dmentioning
confidence: 99%